Determinants of burnout syndrome among nursing students in Cameroon: cross-sectional study - Tsi Njim; Clarence Mbanga; Dave Mouemba; Haman Makebe; Louis Toukam; Belmond Kika; Isabelle Mulango (BMC Research Notes, 2018)
Abstract Objectives Burnout syndrome defined as a state of emotional exhaustion and disengagement; which could reduce optimal healthcare delivery, is relatively common amongst healthcare trainees. We sought to assess the determinants of burnout syndrome amongst nursing students in Cameroon. A cross-sectional study which included 447 nursing students recruited after written informed consent by convenience sampling, was carried out from January to April 2018. A printed self-administered questionnaire assessing burnout using the OLdenburg Burnout Inventory was used. Multivariable linear regression was used to identify independent determinants of burnout syndrome. Results Most (81.17%) of the students were female with the average for disengagement items being 17.10 ± 3.09 (minimum = 8, maximum = 26) and 20.94 ± 3.04 (minimum = 13, maximum = 31) for exhaustion items. After multivariable linear regression analysis, satisfaction with results (RC: − 1.42, 95% CI − 2.52, − 0.32, p value: 0.012) and regret of choice of nursing studies (RC: 2.13, 95% CI 0.58, 3.68, p value = 0.007) were found to be independent predictors of burnout in these students. Early identification of these determinants is required to prevent progression to burnout.